2014
DOI: 10.12816/0010811
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Hypersensitivity and Its Relationship to Preparation Variables in Class I Resin - Based Composite Restorations : Findings from the Practitioners Engaged in Applied Research and Learning ( PEARL ) Network . Part 1

Abstract: Background This study investigated postoperative hypersensitivity at 1, 4, and 13 weeks following resin-based composite (RBC) restorations of occlusal caries and its relationship with prepreparation (baseline) sensitivity and preparation-related variables, including dentin caries activity, cavity dimension and volume, and lesion radiographic visibility. Methods Investigators in a practice-based research network enrolled patients with occlusal caries deemed to require operative treatment. The 45 dental practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…In study teeth with AH at baseline, only about 63 percent experienced elimination of AH after restoration. 2 On further analysis, the study investigators found no relationship in AH outcomes between materials, including consideration of types of liners and bonding agents, and techniques used by the 45 dental practices involved. 3 On the basis of these findings, PEARL clinicians were eager to determine whether including an RMGI liner would reduce POH more than would use of a dentin bonding agent (DBA) alone in RBC restorations.…”
Section: Postoperative Hypersensitivitymentioning
confidence: 88%
See 4 more Smart Citations
“…In study teeth with AH at baseline, only about 63 percent experienced elimination of AH after restoration. 2 On further analysis, the study investigators found no relationship in AH outcomes between materials, including consideration of types of liners and bonding agents, and techniques used by the 45 dental practices involved. 3 On the basis of these findings, PEARL clinicians were eager to determine whether including an RMGI liner would reduce POH more than would use of a dentin bonding agent (DBA) alone in RBC restorations.…”
Section: Postoperative Hypersensitivitymentioning
confidence: 88%
“…The PEARL Network executive management team trained P-Is through use of videos, animated slide presentations and online quizzes in the identification of lesions, caries classification, 15,16 measurement of hypersensitivity to air and cold, SB evaluation, 17 DCA ranking 18 and measurement of preparation dimensions and depth, 2 as well as in treatment procedures. Study participants at baseline and at each recall appointment rated their hypersensitivity to air and cold stimuli by using the Numeric Pain Assessment Scale (NPAS) 19 and completed questionnaires about stimuli that cause hypersensitivity and how the condition affects their QoL.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations